Hubungan Tingkat Pengetahuan Ibu Tentang Kebutuhan Gizi Anak 1 - 4 Tahun di Wilayah Kerja Puskesmas Indrapuri - Lutvia Amellia; Khaira Rizki; Muhammad Daud (Lembaga Pengembangan Kinerja Dosen, 2025)
Nutrition is crucial for children's growth and development. A mother's ability to serve food dishes can affect nutrition knowledge, economic status, and family income. This study aims to determine if there is a correlation between maternal knowledge and the nutritional needs of children aged 1-4 years in Indrapuri Public Health Center. The study used a correlational analytical design with a cross- sectional approach. The sample consisted of 60 respondents, chosen using the total sampling technique. The research was conducted from April 30 to May 26, 2025. Data was analyzed using univariate and bivariate analyses with the Chi-square test. The results showed that out of 60 respondents, most of the respondents were in the lower category of maternal knowledge level, with 57 respondents (95.0%), and 3 respondents (5.0%) were in the acceptable category. Fisher's Exact Test gave a p- value = 0.558 >0.005. These findings indicated no correlation between maternal knowledge levels and the nutritional needs of children. It is expected that the Public Health Center and health officials provide counseling to mothers on the importance of healthy food and nutritional knowledge from the Integrated Health Service Center (Posyandu).